Optimalisasi Peran Polisi dalam Penegakan Hukum Berbasis Humanis dan Profesionalisme - Rizki; Abiezer Manora Purba; Jarot Jati Bagus Suseno; Dianto Gunawan Tamba; Marolop Butar Butar; Jamalum Sinambela (CV Rewang Rencang, 2024)
The article examines the challenges and opportunities in optimizing the role of the Indonesian police (Polri) in humanistic law enforcement. It highlights structural, cultural, and technical barriers, including inefficiencies in bureaucracy, outdated leadership approaches, and inadequate adoption of modern technology. These issues hinder effective policing and diminish public trust. The article also underscores the importance of aligning law enforcement practices with community-specific cultural contexts, such as handling traditional conflict resolution practices like carok in Madura, by employing a humanistic and dialogical approach. To bridge the gap between societal expectations and on-the-ground realities, the article proposes comprehensive strategies. These include capacity-building through humanistic training, emphasizing empathy and cultural understanding, reforming recruitment processes, and leveraging technology for transparency. The implementation of community policing models, such as Polmas, is highlighted as a practical way to foster collaboration between police and communities. The study employs a combination of normative and sociological approaches, drawing on legislation, direct observation, and interviews with police practitioners. By integrating ethical guidelines, continuous training, and community-centric policies, the article advocates for a transformative policing framework that upholds justice, respects cultural diversity, and strengthens public trust. This framework aligns with Indonesia’s Pancasila values, emphasizing fairness and human dignity in law enforcement.